Does loneliness before the age of twelve indirectly affect impaired control over drinking, alcohol use, and problems through perceived stress?. (December 2022) - Berberian, S.; Patock-Peckham, J.A.; Guarino, K.; Gupta, T.; Sanabria, F.; Infurna, F.
Graphical abstract: Highlights: Being a lonely kid (prior to age 12) was linked to more perceived stress today. Being a lonely kid was directly linked to more alcohol-related problems. Perceived stress was directly linked to increase impaired control over alcohol. Stress mediates the indirect link between being lonely and impaired control. Stress affects women more than men as a mediator of loneliness on drinking outcomes. Abstract: Background: Loneliness is the pain of feeling socially isolated from others (Russell et al., 1980). The Stress-Dampening Hypothesis (Marlatt, 1987; Sayette, 1993; Sher, 1987) posits that individuals drink to alleviate negative affect. To date, it has not been determined whether loneliness experienced as a child can indirectly influence at-risk patterns of alcohol use through the mediating mechanism of stress and impaired control. Impaired control over alcohol use (IC) is the difficulty adhering to one's own self-proscribed limits on drinking behaviors (Heather et al., 1993). Impaired control is an at-risk pattern of use that is particularly relevant to emerging adults. Methods: We examined the direct and indirect relationships between childhood loneliness, stress, IC, and alcohol-related problems with a structural equation model. In a college student sample, we utilized a (k = 20, 000) bootstrap technique and a model indirect command in Mplus to examine potential mediational pathways. Cisgender sex was included as a covariate. Results: Loneliness was directly linked to stress as well as to alcohol-related problems. Higher levels of loneliness were indirectly linked to both more alcohol use and alcohol-related problems through more stress and in turn, more impaired control over drinking. Conclusions: The current study is consistent with the Stress Dampening Hypothesis (Marlatt, 1987; Sayette, 1993; Sher, 1987). Our findings suggest that therapeutic interventions combating loneliness in childhood may disrupt the stress-dampening pathway to dysregulated alcohol use in emerging adulthood.